Studi Kebijakan Publik Dana Desa dalam Mengatasi Masalah Kesehatan dan Pendidikan di Desa: Studi Kasus Desa Prasung, Kabupaten Sidoarjo - Febhy Rachmanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the implementation of the Village Fund (Dana Desa) public policy in overcoming health and education problems in Prasung Village, Buduran District, Sidoarjo Regency. The Village Fund policy is a central government instrument designed to accelerate rural development and community welfare. This study uses a qualitative descriptive method with a case study approach. Data was collected through in-depth interviews with village officials, community leaders, and beneficiaries, as well as through observation and documentation studies. The data analysis technique used is an interactive model, examining the context, input, process, and product of the policy implementation. The findings indicate that the Village Fund in Prasung Village has been allocated through community participation in the Village Deliberation (Musdes) for health programs, such as the construction of a Posyandu (Integrated Health Service Post) and health insurance assistance (BPJS), and education programs, including scholarships and school operational assistance (BOS). However, several challenges were identified, including the limited amount of funds compared to needs, uneven distribution of program benefits, and a lack of community involvement in monitoring and evaluation. This study concludes that while the Village Fund policy has made a positive contribution to improving health and education services, its effectiveness is not yet optimal. Recommendations are offered for improving planning, transparency, and community participation to maximize the impact of the Village Fund on human resource development in the village.